Application of the Classical Rayleigh-Ritz Method in Dynamics of Circular Archces - Olszowski, B. (Engineering Transactions, 1993)
The paper deals with Rayleigh-Timoshenko and Bernoulli-Euler models of circular arches with extensible or inextensible axes clamped with free radial sliding at both ends. The general algebraic equation defining the eigenproblem has been derived from Hamilton's principle. Spectral properties of the models were analysed by means of the classical Rayleigh-Ritz approximation method. Eigenfrequencies as functions of the subtending angle of the arch are plotted and tabulated.